2022
DOI: 10.1155/2022/8371440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Dietary Zinc Sources on Growth, Element Deposition, Antioxidation, Lipid Metabolism, and Related Gene Expression in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus)

Abstract: This study investigated the effect of different supplements of Zn on the growth performance, antioxidant, lipid metabolism, and element deposition of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus). A total of 180 juvenile groupers (bodyweight 10.02 ± 0.01  g) were divided into three groups of 20 fish each and fed with ZnSO4, nanozinc oxide (Nano-ZnO), and dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…In our study, the increased contents of CAT and SOD (Table 1) indicated that the antioxidative ability was enhanced by dietary nZnO exposure more than by dietary Zn, as reported in other fish. 32–34 Dietary nZnO may provide Zn and ZnO (incompletely dissolved), and both play physiological roles in organisms. 35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the increased contents of CAT and SOD (Table 1) indicated that the antioxidative ability was enhanced by dietary nZnO exposure more than by dietary Zn, as reported in other fish. 32–34 Dietary nZnO may provide Zn and ZnO (incompletely dissolved), and both play physiological roles in organisms. 35…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the increased contents of CAT and SOD (Table 1) indicated that the antioxidative ability was enhanced by dietary nZnO exposure more than by dietary Zn, as reported in other fish. [32][33][34] Dietary nZnO may provide Zn and ZnO (incompletely dissolved), and both play physiological roles in organisms. 35 Studies on cellular systems following nZnO exposure showed that the GSH content varied as an adaptive response to the generated oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc belongs to transition elements and is found in trace amounts, but it is essential for the proper functioning of millions of enzymes in humans and animals. That's why Zn-based nanoparticles have significant importance by increasing the nutritional requirements of the body (Wang et al, 2022). Several bacteria present in the human digestive tract are hazardous to health, such as Salmonella typhi and Streptococcus aureus (Mak et al, 2022).…”
Section: Zinc and Its Combinationsmentioning
confidence: 99%
“…Zinc (Zn) is one of the microminerals essential for the growth of living organisms [1], as a cofactor for more than 300 enzymes in the body [2]. It plays an important role in the synthesis of proteins, lipids, nucleic acids, and carbohydrates [1,3]. Plants need 20 to 100 ppm of Zn [4].…”
Section: Introductionmentioning
confidence: 99%